2020
DOI: 10.1097/md.0000000000021390
|View full text |Cite
|
Sign up to set email alerts
|

IL-35 polymorphisms and cognitive decline did not show any association in patients with coronary heart disease over a 2-year period

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…However, this relationship should be further examined in larger samples that are followed over time. Conversely, Shi et al (2020) reported IL-35 polymorphisms were not associated with cognitive decline in coronary heart disease patients over 2 years.…”
Section: Discussionmentioning
confidence: 85%
“…However, this relationship should be further examined in larger samples that are followed over time. Conversely, Shi et al (2020) reported IL-35 polymorphisms were not associated with cognitive decline in coronary heart disease patients over 2 years.…”
Section: Discussionmentioning
confidence: 85%